How to Train Students' Mathematical Communication Skills Through Generative Learning?: An Evaluation of Circle Material - Eva Dwi Minarti; Wahyudin Wahyudin; Bambang Avip Priatna Martadiputra (Universitas Muhammadiyah Mataram, 2021)
The purpose of this study is to apply the Generative Learning model to circle material in order to train students' communication skills. In previous research from the author and several studies that have been conducted by researchers, it was found that the Generative Learning model can improve Students' Mathematical Communication skills. On this occasion, it was explained how the Generative Learning Model can train students' communication skills. The research subjects were 25 students of class VIII from one of the State Junior High Schools in Bandung for the 2019/2020 academic year. The method in this research is qualitative. Data obtained through observation and interviews during learning circle material using a generative learning model takes place. The results showed that through the steps in the generative learning model, namely the orientation; the idea stage; the challenge and restructuring; the implementation and; the review stage, can: (1) increase student interaction in learning, (2) stimulate students to create mathematical models; (3) train students in arguing based on analysis of images and concepts; (4) explain ideas, mathematically in writing with pictures.